Effect of COVID-19 inactivated vaccine on anti-Müllerian hormone in Chinese women: a retrospective cohort study - Bao, Mingjie; Xia, Leizhen; Ling, Yan; Wen, Quan; Shen, Xin; Wang, Ting; Qian, Si; Wang, Liqun; Wang, Changhua; Peng, Shiwei; Zhang, Yongping; Zhong, Shaoping; et al. (Frontiers in Endocrinology, 2025)
IntroductionThis study aimed to assess the impact of inactivated COVID-19 vaccine on Anti-Müllerian hormone (AMH) levels in Chinese women.MethodsA retrospective analysis was conducted on women aged 18-45 who had undergone two AMH tests between March 2020 and September 2021. Participants were grouped based on vaccine doses (two- and three-dose), time intervals since vaccination, and manufacturers. The difference in AMH levels and the percentage changes in AMH were measured.ResultsThe results revealed no significant differences in AMH levels between the vaccinated groups (two- and three-dose) and the control group, both in unadjusted and adjusted analyses. Subgroup analysis showed no statistical difference in either absolute or percentage changes of AMH levels among different time-interval groups and manufacturer groups.DiscussionIn conclusion, the number of doses, time interval, and manufacturer of the inactivated COVID-19 vaccine did not affect AMH levels in Chinese women.